Lower limb amputation in England: prevalence, regional variation and relationship with revascularisation, deprivation and risk factors. A retrospective review of hospital data. (December 2014) - Ahmad, Naseer; Thomas, G Neil; Gill, Paramjit; Chan, Colin; Torella, Francesco
Objective: We describe the prevalence of major lower limb amputation across England and its relationship with revascularisation, patient demography and disease risk factors. Design: Retrospective cohort study. Setting: England 1 April 2003 to 31 March 2009. Participants: Patients aged 50–84 years. Main outcome measures: Age standardised prevalence rates were calculated using Hospital Episode Statistics as the numerator with census data as the denominator. The outcome measure 'amputation with revascularisation' was created if an amputation could be linked with a revascularisation. Logistic regression determined the odds of having an amputation with a revascularisation across England. Regression was performed unadjusted and repeated after controlling for demographic (age, sex, social deprivation) and disease risk factors (diabetes, hypertension, coronary heart disease, cerebrovascular disease, smoking). Results: There were 25, 312 amputations and 136, 215 revascularisations, and 7543 cases were linked. The prevalence rate per 100, 000 (95% confidence intervals) for amputation was 26.3 (26.0–26.6) with rates significantly higher in Northern England (North: 31.7; 31.0–32.3, Midlands: 26.0; 25.3–26.7, South: 23.1; 22.6–23.5). The revascularisation rate was 141.6 (140.8–142.3) with significantly higher rates again in Northern England (North: 182.1; 180.5–183.7, Midlands: 121.3; 119.8–122.9, South 124.9; 123.9–125.8). The odds of having an amputation with a revascularisation remained significantly higher in the North (OR 1.22; 1.13–1.33) even after controlling demographic and disease risk factors. Conclusions: There is a North–South divide in England for both major lower limb amputation and revascularisation. The higher odds of having an amputation with a revascularisation in the North were not fully explained by greater levels of deprivation or disease risk factors.